Controlling the nuclearity and topology of cobalt complexes through hydration at the ppm level. Issue 13 (28th February 2020) - Castañeda, Raúl; Rouzières, Mathieu; Clérac, Rodolphe; Brusso, Jaclyn L.
Abstract : Polynuclear cobalt complexes in which nuclearity and topology can be controlled via ppm level control over the degree of hydration (300 vs. 10 000 ppm). Structural and magnetic analysis were used to elucidate the spin state of the cobalt ions. Abstract : Through ppm level control over the degree of hydration ( e.g., 300 ppm vs. 10 000 ppm), the nuclearity and topology of cobalt complexes can be tailored, as demonstrated here. This was achieved by employing N -imidoylamidine ligands, which possess both bidentate and tridentate coordination sites, affording mono-, tri- and hexanuclear cobalt complexes. Structural characterization and magnetic analysis were used to elucidate the spin state of the cobalt ions, which reveal a unique combination of low and high spin states within the polynuclear systems.